Diversity of rDNA in Chilostomella: molecular differentiation patterns and putative hermit types - Hemleben, Vera; Grimm, Guido W.; Kitazato, Hiroshi; Hemleben, Christoph (Anuário do Instituto de Geociências, 2006)
Abstract